Extending the conceptualisation of reflection: making meaning from experience over time. Issue 5 (3rd September 2021) - Palacios, Nahielly; Onat-Stelma, Zeynep; Fay, Richard
ABSTRACT: This article presents a conceptualisation of reflection as a process of meaning-making from experience over time. Existing conceptualisations of reflection, as based on the work of Donald Schön, tend to emphasise the different moments in time in which professionals make meanings of their experience through reflection. However, this article foregrounds another part of his thinking, namely the reflective spiral and its continuity over time. We have developed a conceptual model based on this reflective spiral, a model we exemplify in the analysis of narrative-reflective interviews with one Mexican EFL teacher about her professional sojourner experiences in the UK.